Implementation of Community Education and Knowledge Development in the Utilization of Digital Literacy - Poniyah Simanullang; Selli Dosriani Sitopu; Ester Mei Frida Girsang; Fransiskus Gultom (Postgraduate, University of Mataram, 2023)
This research was conducted in the library of the health center at Posyandu (Integrated Service Post) located in Pasar Borbor Village. Research is carried out once a month in the second week with routine activities for the community. Geographically, Posyandu is far from residential areas, difficult for the community to reach, so there has been a decrease in visits from mothers with toddlers. The purpose of this study was to analyze